The Measurement of X-Efficiency for Banking Companies Listed in Indonesian Stock Exchange: Analysis toward Going Concern Opinion - admin, Muhammad Luthfi Riyadi B42112003 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
Auditors consider the companies’ negative trends before issuing going concern opinion. Standard of auditing (SA) section 341 mentions that financial ratio is one of the negative trend indicators that become the auditors’ consideration. Many studies are conducted by researchers in in various countries to measure the performance of banking companies in terms of efficiency. One of the studies even mentions that efficiency is one of factors that affect the continuity of companies (going concern). This study is using Data Envelopment Analysis (DEA) to measure the x-efficiency of listed banks in Indonesia and analyze the possibility of issuing going concern opinion. The data used in this paper range from 2010 to 2014, which include 30 banks listed in Indonesia Stock Exchange (IDX). The data are selected by using purposive sampling. The result shows ten companies are feasible for a long-term investment, and three of the companies are capable to achieve the optimum efficiency in 2014. The results also show that companies which have x-efficiency score more than 0.9 have less probability to receive going concern opinion than those with lower scores. Keywords: Data Envelopment Analysis (DEA), Indonesian Stock Exchange (IDX), Going Concern Opinion, Bank Efficiency